(untitled) (The Review of Diabetic Studies, 2024)
Background: Infection control procedures are essential, particularly in an airport like Prince Mohammad National Airport, frequently used by travelers and pilgrims coming for Hajj and Umrah. This study aimed to evaluate the knowledge, attitude, and practice of healthcare workers at Prince Mohammad Airport regarding standard infection control precautions. Methods: This cross-sectional study was conducted online using a validated, modified closed-ended questionnaire. One hundred and seven healthcare workers were selected using convenient sampling. The SPSS program, version 28 analyzed the collected data. Both descriptive and inferential statistics, the Mann-Whitney U test, the Kruskal-Wallis H test, and multiple logistic regression were used. A p-value ≤ 0.05 was considered significant in all tests. Results: A total of 107 HCWs participated in the study. Most of them 99 (92.5%), were male, 78 (72.9%) were aged between 30- 40 years, 66 (61.7%) had less than five years of experience, and the majority of them, 93 (86.9%) received training on infection control standard precautions. Overall, good knowledge, positive attitude, and good practice toward standard precautions were (63.60%), (72.90%) and (90.70%) receptively. The profession and qualification had a significant impact on attitude. Physicians and HCWs with higher education had higher attitude mean scores than others. Conclusion: Most HCWs had good practice, attitude, and knowledge, respectively. Training programs for HCWs may help update and strengthen their understanding of infection control standard precautions.